EMPOWERMENT MEDIA SEBAGAI STRATEGI PENINGKATAN KAPASITAS JURNALISTIK PADA PERS MAHASISWA DI UNIVERSITAS PANCASILA - Iswahyunigtyas, Cici Eka; Salsabila, Aisha Balqis; Widhiawati, Rhirin Agita Tri (As-Sidanah, 2026)
This Community Service (PKM) activity aims to increase the knowledge capacity and critical awareness of the Pancasila University student press regarding the position, vulnerability, and media empowerment strategies. The activity was carried out through initial discussions, observations, and interviews to identify the needs and challenges faced by LPM Gema Alpas KMUP and LPM Suara Ekonomi. The core stage of implementation consisted of socialization and Focus Group Discussions (FGD) with practitioners from the Alliance of Independent Journalists (AJI) and the Greater Jakarta Student Press Forum (FPMJ), with effectiveness measured using pre-tests and post-tests. The results of the activity showed a significant increase in participants' understanding of internal challenges, such as weak organizational structures, editorial policies, and the importance of protecting and maintaining the independence of campus media. Participants also understood that student press empowerment does not depend solely on legal regulations but can be achieved by strengthening capacity, economic independence, and solidarity among student journalists. Through this activity, the Pancasila University student press is expected to transform into an empowered, critical, and independent media capable of carrying out journalistic functions in both academic and public environments.